Morphological and molecular data reveal a new species of Allium (Amaryllidaceae) from SW Anatolia, Turkey - Deniz İsmail Gökhan; Genç İlker; Sarı, Duygu (Phytotaxa, 2015)
Allium undulatitepalum (Amaryllidaceae) is described as a new species from the Antalya Province of Turkey. It belongs to the section Melanocrommyum and is endemic to the south-western region of Turkey. The new species is a close relative of A. orientale, but according to results of the ITS sequences, and based on the morphological differences presented in the description, it is clearly different from its relative. A phylogenetic tree, distribution map, illustrations, pollen and seed microphotographs, karyo-morphology, as well as notes on the biogeography and ecology of the new species are provided.